Genetics of arrhythmogenic right ventricular cardiomyopathy. Issue 5 (6th March 2013) - Campuzano, Oscar; Alcalde, Mireia; Allegue, Catarina; Iglesias, Anna; García-Pavía, Pablo; Partemi, Sara; Oliva, Antonio; Pascali, Vincenzo L; Berne, Paola; Sarquella-Brugada, Georgia; Brugada, Josep; Brugada, Pedro; et al.
Abstract : Arrhythmogenic right ventricular cardiomyopathy is a rare clinical entity characterised by fibro-fatty replacement of myocardium, mainly involving right ventricular free wall, leading to malignant electrical instability and sudden cardiac death. The disease is inherited in up to 50% of cases, with incomplete penetrance and variable phenotypic expression. To date, more than 300 pathogenic mutations have been identified in 12 genes, mainly with autosomal dominant inheritance. Here, we focus on recent advances in the genetics of arrhythmogenic right ventricular cardiomyopathy. Despite continuous improvements, current genotype–phenotype studies have not contributed yet to establish a genetic risk stratification of the disease.